A Concise Review of the Recent Structural Explorations of Chromones as MAO-B Inhibitors: Update from 2017 to 2023 - Reshma Susan Ipe; Sunil Kumar; Feba Benny; Jayalakshmi Jayan; Amritha Manoharan; Sachitra Thazhathuveedu Sudevan; Ginson George; Prashant Gahtori; Hoon Kim; Bijo Mathew (MDPI AG, 2023)
Monoamine oxidases (MAOs) are a family of flavin adenine dinucleotide-dependent enzymes that catalyze the oxidative deamination of a wide range of endogenous and exogenous amines. Multiple neurological conditions, including Parkinson's disease (PD) and Alzheimer's disease (AD), are closely correlated with altered biogenic amine concentrations in the brain caused by MAO. Toxic byproducts of this oxidative breakdown, including hydrogen peroxide, reactive oxygen species, and ammonia, can cause oxidative damage and mitochondrial dysfunction in brain cells. Certain MAO-B blockers have been recognized as effective treatment options for managing neurological conditions, including AD and PD. There is still a pressing need to find potent therapeutic molecules to fight these disorders. However, the focus of neurodegeneration studies has recently increased, and certain compounds are now in clinical trials. Chromones are promising structures for developing therapeutic compounds, especially in neuronal degeneration. This review focuses on the MAO-B inhibitory potential of several synthesized chromones and their structural activity relationships. Concerning the discovery of a novel class of effective chromone-based selective MAO-B-inhibiting agents, this review offers readers a better understanding of the most recent additions to the literature.